2000
DOI: 10.1300/j069v19n01_01
|View full text |Cite
|
Sign up to set email alerts
|

Brain Morphological Changes and Early Marijuana Use

Abstract: These findings suggest that the age at which exposure to marijuana begins is important. Early adolescence may be a critical period for effects that are not present when exposure begins later. These results are discussed in light of reported effects of marijuana on gonadal and pituitary hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(74 citation statements)
references
References 52 publications
1
67
0
6
Order By: Relevance
“…In nonschizophrenic participants with a CUD, grey matter volume was positively correlated with age at onset but not with duration of cannabis use, 26 suggesting that the as sociation between cannabis use and brain volume resulted from abnormal brain development rather than neurodegenera tion caused by cannabis. However, Cousijn and colleagues 27 found that volume reductions between cannabis users and controls did not differ significantly, but still correlated with the amount of cannabis used and the severity of cannabis depend ence.…”
Section: J Psychiatry Neurosci 2015;40(3)mentioning
confidence: 95%
“…In nonschizophrenic participants with a CUD, grey matter volume was positively correlated with age at onset but not with duration of cannabis use, 26 suggesting that the as sociation between cannabis use and brain volume resulted from abnormal brain development rather than neurodegenera tion caused by cannabis. However, Cousijn and colleagues 27 found that volume reductions between cannabis users and controls did not differ significantly, but still correlated with the amount of cannabis used and the severity of cannabis depend ence.…”
Section: J Psychiatry Neurosci 2015;40(3)mentioning
confidence: 95%
“…Existen cambios morfológicos asociados con el consumo temprano de mariguana; por ejemplo, la talla (particularmente en hombres) y el peso durante la edad adulta son menores cuando el consumo se inició antes de los 17 años (Wilson, Mathew, Turkington, Hawk, Coleman, & Provenzale, 2000). Además, existe una reducción en el volumen cerebral total y en el de la sustancia gris, mientras que también se observa un aumento en el volumen de la sustancia blanca (Wilson et al, 2000).…”
Section: Resultados Consumo De Mariguana Y Cambios Morfológicos En Elunclassified
“…As alterações foram mais significativas quanto maiores eram as doses de exposição à Cannabis, sendo estas mais frequentemente localizadas na região do hipocampo. Resultados semelhantes foram encontrados nos estudos de Wilson et al 12 e Matochik et al 13 apesar de seus usuários de Cannabis terem sofrido uma exposição bem menor à droga e terem sido utilizadas técnicas menos sensíveis para a realização dos exames em comparação ao estudo de Yücel et al 6 .…”
Section: Estudos Realizados Com Técnicas De Neuroimagemunclassified
“…A relação entre o uso de Cannabis, funcionamento e morfologia cerebral foi também estudada em 57 usuários crônicos da droga, 32 homens e 25 mulheres 12 . Os autores mediram os volumes cerebrais tais como o volume dos ventrículos, substância branca e cinzenta e cérebro total.…”
Section: Estudos Realizados Com Técnicas De Neuroimagemunclassified
See 1 more Smart Citation